PENGEMBANGAN MEDIA E-MODUL PADA TEMA KAYANYA NEGERIKU SUBTEMA KEKAYAAN SUMBER ENERGI DI IDONESIA KELAS IV SDN 01 PANINGGARAN - Afianida, Afifi; Reffiane, Fine; Saputra, Henry Januar (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
The purpose of this study was to determine the aof the development of the E-Module media the theme of the richness of my country the sub theme of the wealth of energy resources in Indonesia grade IV elementary school 01 Paninggaran. This type of research is R&D (Reseaerch and Development), the procedure of this research uses the procedure of Prof. Sugiyono there are 10 procedures and only 7prpcedures are used. The result of this study indicate that the E-Module media obtained a percentage score of 75.83% (Proper to Use), from material expert validators, material expert 2 and 3 by 80% (Proper to Use). The scores obtained from media expert 1 is 75.83% (Proper to Use), media expert 2 is 88.33% (Very worth using), media expert 3 is 76.66% (Proper to Use). There is also a score obtained from the student response questionnaire with a total score of 87.30% (Very worth using). Learning media is feasible to use based on an assessment by three material and media experts wit valid criteria, and the result of the student response questionnaire show the results are very feasible to use.